Hypertensive encephalopathy and the blood-brain barrier: is δPKC a gatekeeper? - Chou, Wen-Hai (American Society for Clinical Investigation, 2007)
Hypertensive encephalopathy is a life-threatening condition due to elevation of cerebral perfusion pressure beyond the limits of autoregulation. Breakdown of the blood-brain barrier (BBB) leads to cerebral edema and reduced blood flow. In this issue of the JCI, Mochly-Rosen and colleagues demonstrate a novel molecular strategy for preserving the BBB in a model of hypertension-induced encephalopathy (see the related article beginning on page 173). Using a rationally designed peptide inhibitor of δPKC, they stabilized the BBB and improved mortality in hypertensive rats. This study highlights the therapeutic potential of δPKC inhibitors in hypertensive encephalopathy and provides incentive to elucidate δPKC signaling pathways that mediate BBB dysfunction in other disease states.